Unruptured Cerebral Aneurysm Detected after Intravenous Tissue Plasminogen Activator for Stroke - Yukihiro Yoneda; Shinji Yamamoto; Yoshie Hara; Haruo Yamashita (Case Reports in Neurology, 2009)
Therapeutic guidelines of intravenous thrombolysis with tissue plasminogen activator (tPA) for hyperacute ischemic stroke are very strict. Because of potential higher risk of bleeding complications, the presence of unruptured cerebral aneurysm is a contraindication for systemic thrombolysis with tPA. According to the standard CT criteria, a 66-year-old woman who suddenly developed aphasia and hemiparesis received intravenous tPA within 3 h after ischemic stroke. Magnetic resonance angiography during tPA infusion was performed and the presence of a small unruptured cerebral aneurysm was suspected at the anterior communicating artery. Delayed cerebral angiography confirmed an aneurysm with a size of 7 mm. The patient did not experience any adverse complications associated with the aneurysm. Clinical experiences of this kind of accidental off-label thrombolysis may contribute to modify the current rigid tPA guidelines for stroke.